2015
DOI: 10.1088/1748-6041/10/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of nanocrystalline TiO 2 coatings in relation to the in vitro plasma protein adsorption

Abstract: This study reports on the selective adsorption of whole plasma proteins on hydrothermally (HT) grown TiO2-anatase coatings and its dependence on the three main surface properties: surface charge, wettability and roughness. The influence of the photo-activation of TiO2 by UV irradiation was also evaluated. Even though the protein adhesion onto Ti-based substrates was only moderate, better adsorption of any protein (at pH = 7.4) occurred for the most negatively charged and hydrophobic substrate (Ti non-treated) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…The streaming potential measurements showed that all the surfaces were negatively charged at physiological pH, although to a different extend according to the chemical composition and surface functionalities [3]. However, different f-values were achieved for the same substrate when calculated by Eq.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The streaming potential measurements showed that all the surfaces were negatively charged at physiological pH, although to a different extend according to the chemical composition and surface functionalities [3]. However, different f-values were achieved for the same substrate when calculated by Eq.…”
Section: Resultsmentioning
confidence: 96%
“…For this reason the study of the implant surface charge, in addition to the surface roughness and wettability, is fundamental to predict the kind and extent of the biological interaction during the first stage after the material insertion in the body. In a previous study [3] we showed how the abovementioned characteristics influenced the adsorption of the plasma proteins on HT TiO 2 -anatase coatings on titanium for hard tissue replacement. The HT surfaces behaved more hydrophilic than the non-treated titanium (Ti NT) and owned an additional nano-roughness, due to the nano-crystals, as evident from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the choice for the most suitable surface modification technique, the evaluation of the physico-chemical properties of a biomaterial surface is compulsory for the proper design of body implants and to predict a priori the influence of the material properties on the events occurring at the bio-interface [12, 13]. In fact, the surface properties are responsible for the interactions with the surrounding tissues and, influencing the “race for the surface” between cells and bacteria [14], affect the consequent acceptance of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated by surface streaming potential studies 21 that after irradiation of the HT-anatase coatings the amount of hydroxyl groups on the surface was strongly enhanced; moreover, Han et al 13 reported that the amount of negatively charged, basic Ti-OH groups after UV irradiation was increased and the treatment helped the apatite-forming ability of the SaOS-2 cell adhesion on micro-arc oxidized Ti-surfaces. In accordance with Tengvall and Lundstrom, 46 the creation of a highly hydroxylated surface improved the HT-coating reactivity with the surrounding ions, proteins and cells.…”
Section: Hmscs Under Osteogenic Stimulusmentioning
confidence: 99%